Penurunan Kadar Air Keseimbangan dan Peningkatan Stabilitas Dimensi Kayu dengan Pemanasan dan Pengekangan Reducing Equilibrium Moisture Content and Improving Dimensional Stability of Wood through Heating and Restraining - Zahrial Coto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
This research was intended to find out the effect of heating (drying at 100ºC) and heating plus restraining to the Equilibrium Moisture Content (EMC) condition and dimensional stability of four Indonesian woods. Tangential board samples about 25 cm long, 15 cm wide, 2.5 cm thick, and five replications were dried at 50ºC followed by increasing drying temperature up to 100ºC for heating treatment. Samples for multiple heating were air-dried followed by reheating at 100ºC. Samples for heating plus restraining were restrained immediately by two U-steel plates connected with four nuts and bolts. All samples were air dried for one week and measured (length, width and thickness) to the nearest 0.01 mm and weighted to the nearest 0.01 g.  Samples, 2.5 cm along the grain were produced from the air-dried boards. Five samples were produced from control boards, four for the effect of time and one for control. One sample was produced from each of the three treatments. All samples were air dried and weighted to the nearest 0.01 g measured (tangential direction) to the nearest 0.01 mm. After conditioning at 50ºC (Relative Humidity = RH around 20%), all samples were re-measured and re-weighted, followed by oven dried. Moisture content at air dried and 20% RH as well as shrinkage from air dried to 20% RH were calculated.Result of the study showed that all three treatments significantly reduced the EMC condition around 2~4%. The highest decrease in EMC was observed for multiple heating treatments. No significant effect was observed for the EMC condition by restraining. All three treatments did not decrease the Rate of Dimensional Change